How many solutions does this equation have?

16q + 18 - 6 = 13q - 18

1 answer

To find the number of solutions to the equation \( 16q + 18 - 6 = 13q - 18 \), we start by simplifying the left side:

\[ 16q + 18 - 6 = 16q + 12 \]

Now, we can rewrite the entire equation:

\[ 16q + 12 = 13q - 18 \]

Next, we will isolate the variable \( q \) by moving all terms involving \( q \) to one side and constant terms to the other side. We can subtract \( 13q \) from both sides:

\[ 16q - 13q + 12 = -18 \]

This simplifies to:

\[ 3q + 12 = -18 \]

Now, we will subtract 12 from both sides:

\[ 3q = -18 - 12 \] \[ 3q = -30 \]

Next, we divide both sides by 3 to solve for \( q \):

\[ q = -10 \]

Since we found a single value for \( q \), the equation has one solution.

In conclusion, the original equation \( 16q + 18 - 6 = 13q - 18 \) has only one solution: \( q = -10 \).